Strategi Berargumentasi dalam Menyelesaikan Masalah Hukum - Siti Nur Intihani (Jurnal Hukum Jurisdictie, 2021)
Legal argumentation is the reason for a clear description of the explanation, in the form of a series of logical statements, to strengthen or reject an opinion, stance or idea, relating to the principles of law, legal norms and concrete legal regulations, as well as legal systems and legal discoveries. The study of legal arguments is carried out using normative juridical methods, namely reviewing secondary data in the form of primary, secondary and tertier legal materials. The question that will be studied is how the strategy of argumentation in solving legal problems. The results of the study concluded that actions must be taken to find strong legal arguments in resolving or finding solutions to legal problems, namely by doing: a) Fact Gathering; b) Classification of Legal Issues; c) Identification and Selection of Relevant Legal Issues; d) Legal discoveries relating to Legal Issues; e) Application of the Law. In the application of the law there are often obstacles, including overlapping authorities and conflicts of interest that occur due to differences in interests and differences in how to interpret laws and regulations. In this regard, interpretation, reasoning and legal argumentation are carried out to prevent and overcome overlapping authorities and conflicts of interest and turn it into an arena of cooperation between governments, entrepreneurs, and society. The conclusion of this study is that legal argumentation is a scientific skill in finding legal solutions, a form of analysis to reach a solution is by the existence of legal opinions. A meaningful argument is built only on logic. In other words, a "conditio sine qua non" decision may be accepted, if based on a process of reason, in accordance with the formal system of logic which is an absolute condition for argumentation. In order for an argument to have meaning, a basic material and an appropriate way are needed. The basic material needed to conduct legal agumentation is an understanding of a matter about law related to legal science. The ability to understand basic materials alone is not enough if it is not presented in the right way. For this reason, a mastery of parables is needed in carrying out the thought process to facilitate using legal arguments